Translation Equivalence: It is a Relative and not an Absolute Issue - Mohammed Nihad Ahmed (PROSPECTIVE RESEARCHES, 2023)
The main aim of this study is to manage one of the corpus tenets of translation, that is, the issue of equivalence. The traditional view of translation equivalence was fundamentally the linguistic and semantic representation of thoughts while, the modern views assert that equivalence is habitually the way the target text became a closest thread to the source text i.e. the process of simulating the closest construction on target text. Hence, this study tackles the prescriptive cognitive implication of the translating process rather than the descriptive one in order to show that the idea of equivalence is theoretically relative, not absolute and to elucidate the role of the cognitive bias in the translating process. So, the translation equivalence is a matter of approximation, because of the existence of several cultural figurative tropes within the text; those which constitute a meaning loss phenomenon. In the light of this view program, some Qur’anic texts were exemplified to show the degree of meaning loss. The translator’s ability to select the closest and suitable equivalent reduces the amount of meaning loss and achieves the comprehension phase to the target receptors through rendering some of the Glorious Qur’anic texts. In this respect, the study concluded that the translator may face ubiquitous figurative tropes within the source textual material. Thus, s/he tries to manipulate it cognitively to warrant the comprehending phase to the target receptors. The study sees that the issue of equivalence is a matter of approximation, because of the differences in many cultural and conceptual considerations among languages. Meaning network among languages of the world draws upon the conceptualizing elaboration that are structurally, semantically and schematically represented mentally, albeit the idea that the selection of equivalence in translating relies not only on the semantic properties but on also the conceptual mappings and pragmatic manipulation that would cause meaning loss throughout translating.